Komunikasi Simbolik Dalam Tradisi Megibung di Kota Mataram - Karisma, Komang; Listiawati, Ni Putu; Rasmini, Ni Wayan; Suarjaya, I Nyoman Alit (IAHN Gde Pudja Mataram, 2023)
Communication is very important for human survival. Symbolic communication is communication carried out through agreed or conventional symbols. Cultural values are symbolic communication used to communicate meaning to society. The megibung tradition is a culture that has symbols and cultural values that must be understood by the community. This research aims to explore symbolic communication in the megibung tradition. This research uses a qualitative research method with a phenomenological approach. The data collection techniques used were observation, interviews and documentation. The data obtained was then analyzed through three stages, namely data reduction, data presentation and data conclusion. The results of this study show that symbolic communication in the megibung tradition is found in the management, order and activities of society, namely a symbol that communicates meaning to society, such as tools, materials, moral values, language, symbols, gestures, time and vocals.